Curriculum Evaluation of Light Vehicle Engineering Department with Discrepancy Model as Per Industry Needs - Aprianto, Anggi; Rizal, Fahmi; Lapisa, Remon; ., Ambiyar; Wakhid, Wakhinuddin; ., Sukardi; Riyanda, Afif Rahman (LPPM Undiksha, 2020)
The implementation of the curriculum as per industrial needs should be improved in terms of qualifications of teachers, tools, practicum materials, and the use of learning models as per industry needs. This study aims to evaluate the used curriculum of light vehicle engineering department as per industry needs. This study uses discrepancy evaluation model (design, installation, process, product and comparison) that describes the implementation of curriculum according to the industry needs from various aspects, namely: design, installation, process, product and comparison. The study results concluded that achievement level of curriculum implementation as needed in the design component obtained an average score of 4.28 (83.17%) classed in a good category; installation components get an average score of 3,502 (78.47%) classified in sufficient categories; process components get an average score of 4.05 (81.75%) classed in a good category; and product components that scored an average of 4.02 (81.26%) classified in a good category. As well as in the comparison component that obtained an average score of 3,324 (74.27%) classified in sufficient categories. The implementation of vocational school curriculum majoring in light vehicle engineering as a whole is categorized as sufficient. Therefore, it needs a follow-up from the relevant parties for a better implementation.; one of which is by revising the curriculum to fit the needs of the industry.